"Macroeconmics, prices, and quantities" - "Tobin , James (ed.)" (Oxford, 1983)
Important new theoretical developments, such as implicit contract search. have radically altered our understanding of labour market The implications of this new concept for macroeconomics and the perennial problems of inflation and unemployment has not been adequately explored before now. This important new book, inspired by the work of the late Arthur M. Okun, attempts a thorough examination of contemporary macroeconomic behaviour. It is concerned with product, labour and asset markets, and how these markets relate to macroeconomic policy.
Keywords: Macroeconomics